Evaluation of Folic Acid Deficiency Anaemia in Predialysis Chronic Kidney Disease Patients: A Hospital-based Study - Mazumder, Ripon Chandra; Sarker, Supriya; Islam, Saiful; Ahmed, ATM Faruque; Halder, Ganesh Chandra; Khan, Sadiqul Islam (Eastern Medical College Journal, 2024)
Background: Chronic kidney disease (CKD) is defined as decreasing kidney function for more than 3 months. Anemia is a common complication of CKD due to a decrease in the hormone erythropoietin related to hemoglobin levels. Folic acid helps with the process of nucleoprotein synthesis and erythropoiesis maintenance.Objectives: The aim of the study was to determine the folic acid level in predialytic anaemic chronic kidney disease patients. Methodology: It was a cross-sectional study conducted in the department of Nephrology of Eastern Medical College & Hospital from September 2020 to August 2021 on predialysis CKD anaemic patient of stage-3 to stage-5. A total of 100 subjects were selected by purposive sampling. The age group was 18 to 70 years. Results: Among the 100 subjects mild, Moderate and Severe aneamia were found in 27%, 44% and 29% respectively. Maximum cases showed normocytic normochromic anaeamia (54%) and 7% cases showed macrocytic aneamia. Serum folic acid levels were found to have decreased in 1 (16.7%), 2 (8.33%) and 7 (10.0%) cases and increased in 2 (33.3%), 5 (20.83%) and 21 (30.0%) cases in stage-3, stage-4 and stage-5 respectively. Conclusion: Anemia is a frequent complication of chronic kidney disease. Inadequate production of erythropoietin by the failing kidneys leads to decreased stimulation of the bone marrow to produce red blood cells. Folic acid deficiency may represent an influential factor in renal anemia. Eastern Med Coll J. July 2023; 8 (2): 13-18